The Influence of Joy and Coolness on Willingness to Make In-Game Purchases Among Mobile Legends: Bang Bang Players Through the Mediating Roles of Game Experience and Immersion - Nur Ilma Shafarisa; Fresha Kharisma (LPPM of NAROTAMA UNIVERSITY, 2026)
Purpose: This study aims to analyze the influence of joy and coolness on willingness to make in-game purchases among Mobile Legends: Bang Bang (MLBB) players in Indonesia, with game experience and immersion serving as mediating variables. Design/methodology/approach: A quantitative explanatory approach was employed using an online questionnaire distributed to 100 active MLBB players across Indonesia who had previously made in-game purchases. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with bootstrapping procedures via SmartPLS software.. Findings: Of 13 hypotheses tested, three were supported. Joy significantly and positively influenced game experience (? = 0.549, p < 0.001), as did coolness (? = 0.264, p = 0.002). Together, these variables explained 54.6% of the variance in game experience. Immersion emerged as the sole significant direct predictor of willingness to make in-game purchases (? = 0.344, p = 0.001). All proposed mediation paths through game experience, immersion, and sequential chain mediation were not statistically supported. Research limitations/implications: The sample size of 100 respondents limited statistical power for detecting indirect effects. The coolness construct also showed suboptimal reliability and convergent validity, requiring instrument refinement in future research. Practical implications: Game developers and marketers should prioritize strategies that deepen player immersion — such as enriching gameplay mechanics, developing emotionally resonant narratives, and offering exclusive in-game items — as immersion is the most direct driver of in-game purchase intentions. Originality/value: This study integrates the Hedonic Motivation System Adoption Model (HMSAM) with coolness theory in a single empirical model within the Indonesian mobile gaming context, providing novel insights into the role of immersion as a critical gateway to in-game purchasing behavior. Paper type: Research paper